Extended TODIM method based on normal wiggly hesitant fuzzy sets for deducing optimal reinforcement condition of agro-waste fibers for green product development. (10th June 2021) - Zindani, Divya; Maity, Saikat Ranjan; Bhowmik, Sumit
Abstract: Green composites from agro-waste have gained exponential interests within the scientific domain owing to the increasing environmental concerns associated with the burning of crop residue. Such composites are being designed to produce green products (particleboards in the present case) that addresses the challenges confronted by the agricultural sector, meeting the technical, economic and environmental sustainability goals. However, there are challenges associated with the identification of optimum processing parameters to obtain the suitable green composites from agro-waste in accordance with the industrial requirements. The present work therefore aims to investigate the performance of bio-epoxy based composite particleboards derived using various weight percentages of punica-granatum agro waste treated with aqueous solution sodium bicarbonate for different time duration. To achieve the aforementioned objective, a novel decision making framework based on prospect theory has been proposed that makes decision under hesitant fuzzy environment by modeling the experts' preferences using Normal Wiggly Hesitant Fuzzy Sets (NWHFS). Proposed decision making framework investigates to identify the optimal set of process parameters (wt% and time duration of chemical treatment) to achieve the best particleboard that meets optimally the technical, environmental and economic requirements. It has been revealed through the application of the proposed decision making framework that the green composite particleboards fabricated with 30% agro-waste and 5 days chemical treatment have the best achievable technical, environmental and economic indicators. The validity, correctness and the robustness of the rankings have been revealed through the sensitivity analysis approach and solving past case studies. The case under consideration has also been solved by other extant fuzzy TODIM approaches. Henceforth, the proposed decision making framework tends to provide the designers a tool to deduce the set of optimum parameters for the green composites from agro-waste that can be employed to explore the possibilities of designing green products and therefore aid in meeting the sustainable goals. Graphical abstract: Image 1 Highlights: Identification of optimal reinforcement condition of agro-waste fibers for green product development. A dedicated decision support framework based on prospect theory for identification of optimal reinforcement condition. Consideration of technical, economic, environmental and socio-cultural indicators while evaluating the material alternatives. Comprehensive analysis of the ranking results obtained by employing proposed decision making framework.